Decreased expression of class III β-tubulin is associated with unfavourable prognosis in patients with malignant melanoma. Issue 1 (February 2016) - Shimizu, Akira; Kaira, Kyoichi; Yasuda, Masahito; Asao, Takayuki; Ishikawa, Osamu
Abstract : Class III β-tubulin (TUBB3) has been recognized as being associated with resistance to taxane-based regimens in several cancers. However, little is known about the clinicopathological significance of TUBB3 expression in patients with cutaneous malignant melanoma. The aim of this study was to examine the prognostic significance of TUBB3 expression in cutaneous malignant melanoma. A total of 106 patients with surgically resected cutaneous malignant melanoma were assessed. Tumour sections were immunohistochemically stained for TUBB3, Ki-67 and microvessel density with CD34. TUBB3 was highly expressed in 80% (85/106) of patients. No statistically significant relationship was observed between the high expression of TUBB3 and any variables. On univariate analysis, ulceration, disease stage, TUBB3 and CD34 revealed a significant relationship with overall survival and progression-free survival. Multivariate analysis confirmed that a low TUBB3 expression was an independent prognostic factor for poor prognosis of cutaneous malignant melanoma. The decreased expression of TUBB3 could be a significant marker for predicting unfavourable prognosis in patients with cutaneous malignant melanoma.